Electric field tuning of a nickel zinc ferrite resonator by non-linear magnetoelectric effects - Maksym Popov; Alexander Machi; Jerad Inman; Rao Bidthanapally; Sujoy Saha; Hongwei Qu; Menka Jain; Michael R. Page; Gopalan Srinivasan (Scientific Reports, 2023)
Abstract The nature of nonlinear magnetoelectric (NLME) effect has been investigated at room-temperature in a single-crystal Zn substituted nickel ferrite. Tuning of the frequency of magnetostatic surface wave (MSSW) modes under an applied pulsed DC electric field/current has been utilized to probe the effect. The frequencies of the modes at 8–20 GHz were found to decrease by ~ 400 MHz for an applied DC power P of ~ 100 mW and the frequency shift was the same for all of the MSSW modes and linearly proportional to P. A model is proposed for the effect and the NLME phenomenon was interpreted in terms of a reduction in the saturation magnetization due to the DC current. The decrease of magnetization with applied electric power, estimated from data on mode frequency versus P, was − 2.50 G/mW. The frequency tuning efficiency of the MSSW modes due to NLME effects in the ferrite resonator was found to be 4.1 MHz/mW which is an order of magnitude higher than the shift reported for M-type strontium and barium hexaferrite resonators investigated earlier. The spinel ferrite resonator discussed here has the potential for miniature, electric field tunable, planar microwave devices for the 8–20 GHz frequency range.